TINJAUAN YURIDIS TENTANG SISTEM PERADILAN PIDANA - Ida Rahma (Hukum Keluarga Islam IAIN LANGSA, 2017)
The function of criminal law aims to prevent future crimes in order toprevent the occurrence of criminal countermeasures. The criminal itself is asanction or a sorrow that tells. Criminal law is a rule of law or a set of rules orlegal norms that regulate an act which is a criminal act, when an act is declared asa criminal act and set the effect (witness) given in reaction to the act that violatesthe rule of criminal law. The function of the criminal law itself is to provide acriminal to those who violate the penal law through state equipment, in order tomaintain public order. Law enforcement is the activity of harmonizingrelationships of values that are outlined in the rules and attitude of acts as a seriesof the final value of the termination to create as social enginering, maintaining andmaintaining as the social control of social interaction, whether it is a preventiveaction (preventive) ) As well as acts of eradication (repressive).